Experiencia de la incorporación de una Evaluación Clínica Objetiva Estructurada en el curso de Ginecología de la carrera de medicina y cirugía de la Universidad de Costa Rica. - Núñez, David Garbanzo (2019)
The Structural Objective Clinical Evaluation (OSCE) is an evaluative tool in clinical and practical aspects that are sometimes not taken in the written test in the clinical courses of the medicine career. Gynecology course (ME 4013 group 01) incorporated an OSCE experience in both semesters of 2018, three procedure stations were use (PAP, long-term contraception placement) and two decision-making (contraceptive choice and complication management). The students valued this activity as positive: "There is a real interaction with the patient and allows to make dynamic decisions regarding the patient management". Aspects to improve were found: the balanced distribution of the stations of the procedures and the reasoning, as well as the clarity of the instructions during the test. The OSCE is a tool that can enrich the already known evaluative method